UPAYA PERLINDUNGAN HUKUM BAGI KURIR MITRA KERJA DALAM PROSES LAYANAN CASH ON DELIVERY (COD) - Febronia Juniati Sanjaya; Krisnadi Nasution (Gapenas Publisher, 2023)
At this moment, business transactions can be done remotely or online, such as through the Grab application. Even though it is done online, payment for business transactions through Grab can be paid in cash when the goods have been received by the buyer, called the Cash On Delivery (COD) service. In business transactions through the Grab application, Grab partners act as couriers to deliver goods from sellers to buyers. The COD system in online transactions has the validity regulated in Pasal 1458 KUHPerdata which states that,